Differential Roles of Akt, Rac, and Ral in R-Ras-Mediated Cellular Transformation, Adhesion, and Survival - Osada, Masako (American Society for Microbiology, 1999)
Multiple biological functions have been ascribed to the Ras-related G protein R-Ras. These include the ability to transform NIH 3T3 fibroblasts, the promotion of cell adhesion, and the regulation of apoptotic responses in hematopoietic cells. To investigate the signaling mechanisms responsible for these biological phenotypes, we compared three R-Ras effector loop mutants (S61, G63, and C66) for their relative biological and biochemical properties. While the S61 mutant retained the ability to cause transformation, both the G63 and the C66 mutants were defective in this biological activity. On the other hand, while both the S61 and the C66 mutants failed to promote cell adhesion and survival in 32D cells, the G63 mutant retained the ability to induce these biological activities. Thus, the ability of R-Ras to transform cells could be dissociated from its propensity to promote cell adhesion and survival. Although the transformation-competent S61 mutant bound preferentially to c-Raf, it only weakly stimulated the mitogen-activated protein kinase (MAPK) activity, and a dominant negative mutant of MEK did not significantly perturb R-Ras oncogenicity. Instead, a dominant negative mutant of phosphatidylinositol 3-kinase (PI3-K) drastically inhibited the oncogenic potential of R-Ras. Interestingly, the ability of the G63 mutant to induce cell adhesion and survival was closely associated with the PI3-K-dependent signaling cascades. To further delineate R-Ras downstream signaling events, we observed that while a dominant negative mutant of Akt/protein kinase inhibited the ability of R-Ras to promote cell survival, both dominant negative mutants of Rac and Ral suppressed cell adhesion stimulated by R-Ras. Thus, the biological actions of R-Ras are mediated by multiple effectors, with PI3-K-dependent signaling cascades being critical to its functions.